Komunikasi Efektif Sebagai Strategi Psikologi dalam Meningkatkan Kinerja dan Penyelesaian Konflik Organisasi - Nia Ramadhani; Manzil Silsa Sabila; Mahda Sakinah; Firman Hakiki; Mu’allimin Mu’allimin (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
Organizational communication is crucial in enhancing performance, productivity, and creating a harmonious work environment. In management psychology, communication serves as a tool for information exchange and a means to build interpersonal relationships and manage conflicts. This study employs a literature review method by analyzing five key articles related to organizational communication. The results indicate that effective communication can enhance motivation, reduce conflicts, and strengthen employee engagement. Barriers such as perceptual differences and information overload can be addressed through appropriate communication strategies, including the use of technology and psycholinguistic approaches. Therefore, good communication should be a priority within organizations to create a more efficient and collaborative work system